The role of Epistemic Communities in the evolution of trade policy in post-apartheid South Africa - Ncongwane, Precious Nobantu (My University, 2012)
The research is a discussion and analysis of the evolution of trade policy in post-apartheid South Africa. It investigates the role of Epistemic Communities in this evolution by making use of Sikkink and Keck’s understand of the mechanism of persuasion, namely information, leverage, symbolic and accountability politics. The epistemic communities analysed are the World Bank and the Congress of South African Trade Unions (COSATU) and the AsgiSA Task Force. An analysis of how the COSATU advocated for the implementation of the Reconstruction and Development Programme (RDP) will be made. The World Bank’s role in the adoption of the Growth, Employment and Redistribution Strategy (GEAR) will also be analysed. Then the role and relation of the AsgiSA Task Force and the government of South Africa in the adoption of the Accelerated and Shared Growth Initiative for South Africa (AsgiSA) will be discussed. In light of the above, the research seeks to show that epistemic communities played an important role in influencing government decision making processes where trade policy is concerned